Ijarah dalam bisnis sewa mobil mewujudkan transaksi bebas riba - Khasanah, Uswatun (Maliki Interdisciplinary Journal, 2025)
In the perspective of Islamic economics, transactions that contain elements of usury and gharar are included in the category of muamalah which are prohibited because they are contrary to the principles of justice, transparency, and blessings in doing business. Therefore, a system is needed that is able to offer halal alternatives in leasing practices, one of which is through the application of ijarah contracts. The purpose of writing this article is to find out the role of ijarah contracts in the car rental business to realize usury-free transactions. The type of research in this study is library research, which is research through literature or literature studies. The application of ijarah contracts in the car rental business is a good and strategic solution in realizing economic transactions that are free from elements of usury, gharar, and injustice. The ijarah contract provides a clear, fair, and sharia-compliant transaction structure, focusing on the utilization of goods without transferring ownership. In practice, ijarah provides protection for both parties through a transparent agreement.